Factors controlling shallow subsurface dissolved reactive phosphorus concentration and loss kinetics from poorly drained saturated grassland soils. Issue 2 (1st February 2023) - Smith, Gen J.; McDowell, Richard W.; Daly, Karen; Ó hUallacháin, Daire; Condron, Leo M.; Fenton, Owen
Abstract: Shallow subsurface pathways dominate dissolved reactive phosphorus (DRP) losses in grassland soils that are: poorly drained, shallow, or have a perched water table in wetter months causing saturation‐excess runoff. Saturated conditions can lead to anoxia, which can accelerate phosphorus (P) loss. Two scales of investigation were utilized in this study. First, at the field scale, soil cores were extracted to 2.5 m, subdivided and samples extracted using water extractable P (WEP) and sodium‐bicarbonate‐dithionite extractable P (NaBD‐P). Second, at the laboratory scale, detailed incubation studies using field‐moist grassland topsoils from sites in Ireland and New Zealand examined the kinetics of WEP under anoxic (WEPanox ) and oxic (WEPox ) conditions with imposed temperature and soil P fertilizer input treatments. Results from soil‐core samples showed that redox‐sensitive NaBD‐P concentrations were depleted where artificial drainage lines were installed (100 cm deep), but WEP concentrations available to shallow flow were enriched in topsoil. The laboratory scale incubation experiment investigated the influence of temperature (3 vs. 18 °C), anoxia (designed to simulate saturation following a rainfall event), and superphosphate fertilizer (10 to 60 kg P ha −1 yr −1 ) on WEP concentrations over 24 h in three grassland topsoils (clay, silt, and sandy loam textures). Concentrations increased with fertilizer rate, temperature, and—in two soils—anoxic conditions. This was commensurate with nitrate (NO3 − ) depletion and the reductive dissolution of iron and manganese. The release of P during anoxia was complete within 24 h. The results highlighted late winter to spring as the riskiest period for topsoil P losses in shallow subsurface flow due to wet soil conditions, increasing temperatures, and low soil NO3 − concentrations. This knowledge highlights the necessity to consider and refine tests used to assess topsoil P loss risk, where in the landscape P losses are likely, and what strategies can be used to mitigate losses. Core Ideas: Reductive dissolution reactions increasing phosphorus (P) release can take <24 h. Oxygen, temperature, and fertilizer affected the amount and rate of P loss. Late winter to spring was the riskiest period for topsoil P losses in shallow subsurface flow. P losses occur due to wet soil conditions, increasing temperatures, and low soil nitrate.